Energy Scarcity Promotes a Brain-wide Sleep State Modulated by Insulin Signaling in C. elegans - Susanne Skora; Fanny Mende; Manuel Zimmer (Cell Reports, 2018)
Neural information processing entails a high energetic cost, but its maintenance is crucial for animal survival. However, the brain’s energy conservation strategies are incompletely understood. Employing functional brain-wide imaging and quantitative behavioral assays, we describe a neuronal strategy in Caenorhabditis elegans that balances energy availability and expenditure. Upon acute food deprivation, animals exhibit a transiently elevated state of arousal, indicated by foraging behaviors and increased responsiveness to food-related cues. In contrast, long-term starvation suppresses these behaviors and biases animals to intermittent sleep episodes. Brain-wide neuronal population dynamics, which are likely energetically costly but important for behavior, are robust to starvation while animals are awake. However, during starvation-induced sleep, brain dynamics are systemically downregulated. Neuromodulation via insulin-like signaling is required to transiently maintain the animals’ arousal state upon acute food deprivation. Our data suggest that the regulation of sleep and wakefulness supports optimal energy allocation.